Initial Requirements for the Prototyping of an App for a Psychosocial Rehabilitation Project: An Integrative Review - Alfredo Ardisson Cirino Campos, Fagner; Feitosa, Fabio Biasotto; Moll, Marciana Fernandes; Reis, Igor de Oliveira; Sánchez García, José Carlos; Ventura, Carla Aparecida Arena (International journal of environmental research and public health, 2025)
The Psychosocial Rehabilitation Project (PRP) is a tool designed to structure and organize mental health care, guided by the theoretical and practical principles of Psychosocial Rehabilitation (PR). This article aims to identify the initial requirements for the prototyping of a “Psychosocial Rehabilitation Project App”. To achieve this, an integrative review was conducted with the research question: what initial requirements are important to compose the prototype of the “Psychosocial Rehabilitation Project App” in mental health? In the search process, 834 articles were identified and exported to the online systematic review application Rayyan QCRI, resulting in 36 eligible articles for this study, along with one app. The reading of this material allowed the elicitation of three themes: privacy and data protection policy; design; and software and programming. The prototyping of the “Psychosocial Rehabilitation Project App” should prioritize data security and protection, simplicity in design, and the integration of technological resources that facilitate the management, construction, monitoring, and evaluation of psychosocial rehabilitation projects by mental health professionals.